Effects of chlorogenic acid on capacity of free radicals scavenging and proteomic changes in postharvest fruit of nectarine. - Yu Xi; Wenxiao Jiao; Jiankang Cao; Weibo Jiang (PLoS ONE)
To study how chlorogenic acid affects changes of reactive oxygen species (ROS) and the proteins involved in ROS scavenging of nectarine during storage time, the fruits were treated with chlorogenic acid (CHA) then stored at 25°C for further studies. The CHA-treatment significantly reduced O2-· production rate, H2O2 content, and membrane permeability of nectarine fruit during storage. The key proteins related the nectarine fruit senescence during storage were identified by two-dimensional electrophoresis and MALDI-TOF/TOF. Level and enzymatic activity of peroxidase were reduced, while both the protein levels and the enzymatic activities of superoxide dismutase, glutathione reductase, glutathione-s-transferase and monodehydroascorbate reductase were enhanced in nectarine fruit treated with CHA. In addition, levels of several pathogen-related proteins were also enhanced by CHA-treatment. Taking together, the present study showed that CHA could influence changes in defense related proteins and reduced oxidative damage in nectarine fruit during postharvest ripening.